“Alle Apparate abschalten.” Conceiving Love and Technology with Heidegger And Kittler - Robert A. Winkler (On_Culture, 2020)
This article explores Friedrich Kittler’s conception of the intersection of love with modern technology and illustrates the theoretical insights gained by considering Spike Jonze’s film Her (2013). The German media theorist Friedrich Kittler (1943–2011) was among the first to study the discursive and material implications of modern technologies. Recent scholarship has stressed Kittler’s indebtedness to Martin Heidegger’s philosophy of technology. Accordingly, Kittler thinks through the latter’s contention that it is in and through modern technology that human beings are possibly confronted with ‘truth events,’ in which the particular time-specific ‘self-unconcealment of being’ takes place — and this unconcealment would not least materialize in the realm of ‘love’ (Gumbrecht 2013; Kittler 2014; Weber 2018).